Study on the effect of 40 Hz non-invasive light therapy system. A protocol for a randomized, double-blinded, placebo-controlled clinical trial - Agger, Mikkel Pejstrup; Horning, Maibritt; Carstensen, Marcus Schultz; Danielsen, Else Rubæk; Baandrup, Anders Olhues; Nguyen, Mai; Høgh, Peter; Miskowiak, Kamilla; Petersen, Paul Michael; Madsen, Kristoffer Hougaard; Kjær, Troels Wesenberg (Frontiers in Aging Neuroscience, 2023)
Introduction With no cure or effective treatment, the prevalence of patients with Alzheimer’s disease (AD) is expected to intensify, thereby increasing the social and financial burden on society. Light-based 40 Hz brain stimulation is considered a novel treatment strategy for patients with AD that may alleviate some of this burden. The clinical trial ALZLIGHT will utilize a novel Light Therapy System (LTS). The LTS uses Invisible Spectral Flicker for non-invasive induction of 40 Hz neural activity. This protocol describes a trial evaluating the efficacy and safety of a light-based 40 Hz brain stimulation in patients with mild-to-moderate AD. Methods 62 patients with mild-to-moderate AD will participate in a randomized, double-blinded, placebo-controlled, parallel-group, and single-center trial. The participants will partake in an enrollment period of 1 month, an intervention period of 6 months, and a 1.5-month post-interventional follow-up period. Prior to the baseline measurement (week 0), the patients will be randomized to either active or placebo intervention from baseline (week 0) to post-intervention follow-up (week 26). Discussion This protocol describes a randomized, double-blinded, placebo-controlled clinical trial that may increase the understanding of the effect of gamma oscillations in the human brain and how it could be utilized as a novel and important tool for the treatment of AD. The effect is measured through a large, multidisciplinary assessment battery. Clinical trial registration:www.ClinicalTrials.gov, (NCT05260177). Registered on March 2, 2022.